Enhancing Sustainability in Urban Transportation with Innovative Mechanical Engineering Solutions for Electric Buses in Jakarta - Sarie, Fatma; Tahir, Abdul; Pahrijal, Rival (West Science Interdisciplinary Studies, 2023)
This study looks into how novel mechanical engineering solutions for electric bus technology in Jakarta could change the industry, with an emphasis on improving sustainability, efficiency, and performance. Quantitative data was gathered through technical inspections, stakeholder questionnaires, and real-time monitoring. According to the results, buses with regenerative braking systems, lightweight construction, and cutting-edge drivetrain technologies consume 15% less energy. A comparative investigation revealed a 12% boost in overall speed and responsiveness and a 20% improvement in braking efficiency. The environmental benefits were highlighted by the environmental impact evaluations, which showed a notable 25% reduction in particulate matter and emissions. Positive responses to surveys conducted among passengers and bus operators demonstrated the practical viability and user pleasure of these advances. Although they recognized the potential, city officials stressed the need for a thorough and gradual implementation strategy. According to the research, creative mechanical engineering solutions might completely transform Jakarta's urban transportation system and serve as a template for effective and sustainable mobility.